Toward Zero Waste: Sustainable Practices in Waste Management at ETUT - Yslam Orazov; Gurbanmyrat Mezilov; Batyr Atdayev; Mahrijemal Annamyradova; Ayshat Ovliyagulyyeva; Yazgul Nurberdiyeva; Serdar Gedayev (Universitas Diponegoro, 2024)
The paper discusses Oguz Han Engineering and Technology University of Turkmenistan's (ETUT) waste management initiatives, particularly its Zero Waste Program aimed at minimizing waste generation and promoting sustainability across campus. Strategies include educational campaigns, eco-friendly purchasing, and collaboration with vendors for waste reduction, reuse, and recycling. ETUT employs structured waste categorization, centralized repositories for reusable items, and a recycling plant with advanced sorting machinery. Innovative methods like paper recycling and composting are used, along with exploring plastic repurposing into fibers and fuel. Organic waste management includes composting, notably reducing landfill waste. Inorganic waste reduction involves paper recycling, plastic conversion, and electronic repair and donation. The program emphasizes waste reduction through recycling and reuse, including upcycling workshops. Hazardous waste from laboratories is managed with local authorities for safe disposal, while relevant associations for environmental safety oversee sewage disposal. These strategies highlight ETUT's commitment to sustainability, positioning it as a regional leader in responsible waste management.